Local anaesthetic inhibition of lidocaine on the growth of streptococcus mutans in vitro - Gostry A. Dohude; Mulyani Rahmah (DiscoverSys Inc., 2022)
Objective: This study aims to determine the effectiveness of lidocaine of local anaesthetic agent in inhibiting the growth of streptococcus mutans bacteria. Material and Methods: This type of research is a laboratory experimental with a post test only control group design. Microorganism used was streptococcus mutans and cultured at the Microbiology Laboratory of the Pharmacy, Universitas Sumatera Utara. The local anaesthetic tested was a solution of lidocaine diluted with NaCl 0.9% to 0.5%, 1%, and 2%. The antibacterial activity test was carried out using diffusion method by dripping 25 µl of lidocaine (0.5%, 1%, 2%), positive control (amoxicillin), and negative control (NaCl 0.9%) on disc paper, then placed on nutrient agar, and incubated. After 24 hours, the inhibition zone formed around the disc paper was observed. Results: Lidocaine showed antibacterial activity with the inhibition zone of 0.5%, 1%, 2% concentration was 6.98 mm, 7.66 mm, 8.36 mm. Then the data was analyzed using the One-way ANOVA test. From these results, there was a significant difference in the mean of the inhibitin zone (p < 0.05) between 0.5%, 1%, and 2% lidocaine, positive control, and negative control. Conclusion: Lidocaine has antibacterial activity against Streptococcus mutans bacteria with an effective concentration of 2%.